Evaluation of Postharvest Behaviour of Bitter Gourd as Influenced by Gamma Irradiation and Modified Atmosphere Packaging - Rashid, MM; Akhther, N; Hassan, MK; Islam, MR; Rafiq, LB (Bangladesh Journal of Nuclear Agriculture, 2023)
An experiment was conducted at the Postharvest Laboratory of Horticulture Division, Bangladesh Institute of Nuclear Agriculture during November to December 2022to examine the effects of different doses of gamma irradiation and Modified atmosphere packaging (MAP) on shelf life and quality of bitter gourd at ambient condition. The experiment comprised ten postharvest treatment viz., T0 =Control (untreated, unwrapped and non-irradiated); T1 =Gourds wrapped in Polypropylene (PP) bag; T2 =Gourds treated with 3% CaCl2; T3 = Irradiated at1000 Gy, T4= Irradiated at2000 Gy, T5 =3% CaCl2+ PP bag, T6 = 1000 Gy+ PP bag, T7 = 2000 Gy+ PP bag, T8 =3% CaCl2, + 1000 Gy+ PP bag and T9 = 3% CaCl2 + 2000 Gy+ PP bag. The single-factor experiment was carried out in a completely randomized design with three replications. Parameters investigated were fruit colour, shrinkage, moisture content, dry matter content, weight loss, disease incidence (DI), disease severity (DS) and shelf life. The minimum weight loss (3.49%), shrinkage (0.00%), DI (11.11%),DS (6.67%) and longest shelf life (10 days) were found in bitter gourds treated with T8 treatment, whereas the maximum weight loss (52.31%), shrinkage (3.89%), DI (77.78%), DS (76.67%) and shortest shelf life (4 days) were T0 treatment at 8 days after storage. The findings would have great impact in reducing enormous postharvest loss of bitter gourd and maintain their quality during postharvest handling and marketing under ambient condition. Bangladesh J. Nuclear Agric, 37(2): 57-68, 2023